2020
DOI: 10.3390/coatings10020161
|View full text |Cite
|
Sign up to set email alerts
|

The Improvement of Hardness and Corrosion Resistance of Electroplated Pd-Ni Film on 316L Stainless Steel by CeCl3

Abstract: By using the methods of XRD, SEM/EDS, electrochemical polarization, and a weight loss test, the effects of the rare earth salt CeCl 3 on the adherence, hardness, porosity and corrosion resistance of an electroplated Pd-Ni film on 316L stainless steel were studied. The results showed that by adding 1.0 g L −1 CeCl 3 in the plating bath, the obtained Pd-Ni film was obviously improved. The grain size was refined, and the microstructure was more compact and uniform. The film hardness and the adherence to the subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Meanwhile, Wang et al reported that the addition of Ce salt refines the grain size, enhances the crack resistance, reduces the pin holes and develops a compact and uniform protective film. This enhances the bonding strength between the substrate and the sealing coating film [26][27][28][29][30]. Furthermore, simulations were performed to evaluate the interface strength of the coating-substrate system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Wang et al reported that the addition of Ce salt refines the grain size, enhances the crack resistance, reduces the pin holes and develops a compact and uniform protective film. This enhances the bonding strength between the substrate and the sealing coating film [26][27][28][29][30]. Furthermore, simulations were performed to evaluate the interface strength of the coating-substrate system.…”
Section: Resultsmentioning
confidence: 99%
“…Ce compounds are widely investigated for future thermal barrier coatings and hydrophobic coatings owing to their high melting point (1060 K), low thermal conductivity (2 W mK −1 ) and easily tailored structures [28][29][30][31][32]. Interest in Ce-based anti-corrosion approach has increased in recent decades owing to their various positive characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…However, when rare earth ions are abnormally co-deposited with other metal ions, they can effectively improve the surface smoothness of the deposition layers. During electrodeposition, the addition of rare earth elements can increase the deposition rate, increase the cathode polarization degree, refine the grain size of the deposition layers and improve their hardness, corrosion resistance [12,13], and other properties [14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the structural characteristics of the coating can be altered by changing electroplating parameters such as temperature, pH, agitation speed, compositional concentration, and current density. Previous studies have focused on the electrodeposition of Pd alloys such as Pd–Ni [9-18], Pd–Ag [19-21], and Pd–Sn [22]. However, only a few studies have been conducted on Pd and Pd-based alloy electrodeposits used as electrical contacts.…”
Section: Introductionmentioning
confidence: 99%